(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Pulses serve as one of the main sources of protein and minerals as well as play a vital socio-economic role in the diet of common people of Bangladesh but these pulses suffer enormous losses due to infestation of a serious insect pest pulse beetle, Callosobruchus chinensis L. As a part of eco-friendly management of this detrimental pest, an experiment was conducted at the laboratory to determine the toxicity of spinosad against the pulse beetle, C. chinensis L. directly by using dry film contact toxicity method and indirectly by treating chickpea seeds. In the direct method spinosad showed contact toxicity and the lethal concentration of spinosad was 117.46, 76.05 and 37.45 ppm at 24, 48 and 72 hours after treatment, respectively. On the other hand, the LC50 values were 990.34, 301.35 and 95.08 ppm after 24, 48 and 72 HAT, respectively as per indirect method. A dose-dependent relation with the mortality was observed by both methods. Spinosad was also significantly effective in reducing the number of eggs (68.00 to 98.60% inhibition over control), adult emergence (56.70 to 100% inhibition over control), percent seed infestation (62.79 to 100% inhibition over control) and seed weight loss (50.81 to 100% inhibition over control). The present results indicated that spinosad could be suggested for the efficient management of C. chinensis in storage. J. Bangladesh Agril. Univ. 16(3): 411–416, December 2018